Analisis Pembelajaran Komunikasi Arab Dalam Pembelajaran Bahasa Arab Di SMA Aisyiyah Boarding School Bandung - Selpi Oktaviani; Maman Abdurrahman (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2021)
This research is motivated by the difficulties experienced by students when learning Arabic communication takes place. Therefore, this study aims to describe Arabic communication learning, starting from planning, processing, evaluation and the obstacles that students feel when learning Arabic communication activities. This research uses a qualitative approach with descriptive methods. The sample in this study were students of class X Social and teachers who taught Arabic communication. Data collection techniques used were observation, interviews, documentation and student questionnaires. To analyze the data, researchers used qualitative data analysis with data verification steps, data presentation and data reduction. The results showed that 1) Arabic communication learning planning by the teacher was well prepared, the teacher used the 2013 curriculum and Arabic communication modules that were compiled by themselves 2) The Arabic communication learning process went well and according to the procedure but there were some students who were slow to understand the material provided by the teacher 3) Evaluation of Arabic Communication learning including daily exams, midterm and final semester exams including oral tests, written tests and group assignments. 4) The obstacles experienced by students in learning Arabic communication, namely; the lack of student interest in learning Arabic, the lack of self-confidence when communicating using Arabic, the difference in the student's school background that makes students' Arabic language skills diverse